Predictors of Iron Supplement Adherence and Hemoglobin Levels Among Adolescent Girls in Bali: A PLS-SEM Analysis - I Gusti Agung Ari Kusuma Yana; Yosi Irawati Wibowo; Antonius Adji Prayitno Setiadi; Cecilia Brata; Gusti Ayu Putu Laksmi Puspa Sari (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Anemia among adolescent girls remains a global public health concern. Adolescence is a critical window of rapid growth and increased iron requirements. The World Health Organization recognizes adolescent anemia as a priority. Although weekly iron supplementation programs have been widely implemented, adherence remains suboptimal. Previous studies have primarily identified associated factors using bivariate or conventional regression approaches, with limited application of multivariate pathway modelling to simultaneously examine determinants of adherence and hemoglobin outcomes. This study aimed to examine predictors of iron tablet adherence and their association with hemoglobin levels among adolescent girls using Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. Methods: A quantitative study with a pretest–posttest one-group design without a control group was conducted. Data were collected using validated questionnaires from adolescent girls (n = 772), of whom 483 participated in final analysis attending schools in Bali, Indonesia, between August and November 2024. Statistical analyses and PLS-SEM were performed to identify key predictors of adherence and hemoglobin levels. Results: A total of 483 adolescent girls participated in the study (response rate: 62.6%). The structural model explained 4.6% of the variance in iron tablet adherence (R² = 0.046) and 38.4% of the variance in hemoglobin levels (R² = 0.384). Family support (? = 0.051; p = 0.041), school support (? = 0.131; p = 0.011), and attitude (? = ?0.071; p = 0.003) significantly predicted adherence. In turn, adherence showed a positive association with hemoglobin levels (? = 0.570; p < 0.000). Conclusion: Family support, school support, and attitude were significantly associated with iron supplement adherence among adolescent girls. Although the explanatory power of the model for adherence was modest, adherence was positively associated with hemoglobin levels at post-test measurement. These findings should be interpreted as exploratory and hypothesis-generating. Multifactorial strategies that strengthen social support and sustained monitoring may enhance the effectiveness of anemia prevention programs among adolescent girls.